2013
DOI: 10.3109/14767058.2013.863864
|View full text |Cite
|
Sign up to set email alerts
|

Myometrial elasticity determined by elastosonography to predict preterm labor

Abstract: Elastosonographic evaluation of uterine myometrium was found to be significantly correlated with cervical length but cervical length measurement is a better predictor for preterm labor than ES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…The investigators reported that transvaginal cervical length is obviously a preferable predictor for preterm labor compared to elastography, in spite of the significant correlation between elastographic assessment of uterine myometrium and transvaginal cervical length. 9 The results of the present study were consistent with the study of Ozkaya et al in that our study revealed a close relation between stiffness of the uterine myometrium and preterm birth. In addition, a linear regression model showed that the ratio of uterine myometrium strain to fat tissue strain was found as the only significant predictor for preterm delivery.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The investigators reported that transvaginal cervical length is obviously a preferable predictor for preterm labor compared to elastography, in spite of the significant correlation between elastographic assessment of uterine myometrium and transvaginal cervical length. 9 The results of the present study were consistent with the study of Ozkaya et al in that our study revealed a close relation between stiffness of the uterine myometrium and preterm birth. In addition, a linear regression model showed that the ratio of uterine myometrium strain to fat tissue strain was found as the only significant predictor for preterm delivery.…”
Section: Discussionsupporting
confidence: 93%
“…Ozkaya et al investigated the efficiency of uterine myometrial elastographic measurements on predicting preterm labor by comparing the outcomes with a widely verified method: cervical length measurement. The investigators reported that transvaginal cervical length is obviously a preferable predictor for preterm labor compared to elastography, in spite of the significant correlation between elastographic assessment of uterine myometrium and transvaginal cervical length . The results of the present study were consistent with the study of Ozkaya et al in that our study revealed a close relation between stiffness of the uterine myometrium and preterm birth.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations